The Settlement and Landscape Context of the Battle of Hastings. Issue 1 (2nd January 2021) - Haslam, Jeremy
Abstract : THIS ARTICLE PUTS FORWARD A MODEL for the development of the settlement and landscape context of the town of Hastings (East Sussex) immediately prior to the battle of Hastings of 1066. It explores the new thesis that a burh or citadel was created on the site of Castle or West Hill at Hastings, the site of the later Norman castle, by King Æthelred II in c ad 990 as one element in a possibly systematic defence of southern England against Viking invaders. The burh was associated with the establishment of a mint, and both led directly to the development of the town of Hastings from that time, together with a probable port and associated ship-building industry. The site of this putative burh, which was likely provided with defences, a tower-nave church and a monumental gateway, survived to be used by Duke William for two weeks in the autumn of 1066 as his military command centre in preparation for the battle which made possible his subsequent conquest of England.